2004
DOI: 10.1002/cbdv.200490021
|View full text |Cite
|
Sign up to set email alerts
|

Main Structural and Stereochemical Aspects of the Antiherpetic Activity of Nonahydroxyterphenoyl‐Containing C‐Glycosidic Ellagitannins

Abstract: Antiherpetic evaluation of five nonahydroxyterphenoyl-containing C-glycosidic ellagitannins, castalagin (1), vescalagin (2), grandinin (3), roburin B (5), and roburin D (7), was performed in cultured cells against four HSV-1 and HSV-2 strains, two of which were resistant to Acyclovir. All five ellagitannins displayed significant anti-HSV activities against the Acyclovir-resistant mutants, but the monomeric structures 1-3 were more active than the dimers 5 and 7. Vescalagin (2) stands out among the five congene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 53 publications
2
49
0
1
Order By: Relevance
“…The 1 H-NMR spectroscopic data of the crude extract of S. cymosum showed signals characteristic of phenolic compounds as the major constituents. Phenolic compounds have received considerable attention because of their therapeutic effects and their favorable antiviral activity (Quideau et al, 2004;Likhitwitayawuid, 2005;Tareq et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The 1 H-NMR spectroscopic data of the crude extract of S. cymosum showed signals characteristic of phenolic compounds as the major constituents. Phenolic compounds have received considerable attention because of their therapeutic effects and their favorable antiviral activity (Quideau et al, 2004;Likhitwitayawuid, 2005;Tareq et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,3,4,6-penta-O-galloyl-β-D-glucose (PGG), a naturally occurring polyphenolic compound abundant in several medicinal plants, was found to exhibit anti-influenza virus activity at non-cytotoxic concentrations. A number of in vitro and in vivo studies have previously shown that PGG exhibits a wide range of biological activities [41], including anti-inflammatory [16], antioxidant [29], anti-angiogenic [25], antitumor [14], antibacterial activity [40], and a broad range of antiviral activity against respiratory syncytial virus (RSV) [39], Hepatitis B virus (HBV) [18] and Herpes simplex virus (HSV) [27][28]31]. Moreover, it has been shown to have an inhibitory effect on viral enzymes such as integrase and reverse transcriptase of human immunodeficiency virus (HIV-1) [1], and NS3 protease of Hepatitis C Virus (HCV) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these two compounds are the likely main polyphenolic constituents in the seed of camu-camu fruit. Vescalagin and castalagin have been isolated from several plants belonging to Fagaceae, Combretaceae, Lythraceae and Myrtaceae (Quideau et al, 2004). Camu-camu belongs to the family Myrtaceae; however, this is the first report of the presence of vescalagin and castalagin in camu-camu.…”
Section: Resultsmentioning
confidence: 92%